Application of FMEA in the automotive industry: Present situation and perspectives in the Republic of Serbia - Tadić Danijela; Banduka Nikola; Petrović Tijana; Komatina Nikola (Trendovi u Poslovanju)
This paper conducts an analysis of the application of FMEA in companies operating in the automotive industry within the territory of the Republic of Serbia, focusing on the current situation and future perspectives. The basic characteristics of implementing this analysis are presented, such as the number of employees involved in the implementation process and the prevalence of different types of FMEA in the considered companies. Additionally, the study presents and analyses the needs for methodological improvements and the adoption of modern tools in conducting FMEA. The aim of this research is to present the current situation and challenges in the application of FMEA in the automotive industry in the Republic of Serbia, as well as to identify possibilities for future improvements.